Rock mechanics as a guide for afficient utilization of natural resources : proceedings of the 30th U. S. Symposium - Khair, A. Wahab; United States Symposium on Rock Mechanics (30th : 1989 : Morgantown ) (Rotterdem : A. A. Balkema, 1989)
51